The functional outcome of hemiarthroplasty with cemented modular bipolar prosthesis in comminuted fracture intertrochanteric femur in elderly population - Das, Mrinmoy; Meena, Ram Khiladi; Prajapati, Pankaj; Yadav, Bhavya Raj Singh (International Journal of Research in Orthopaedics, 2025)
Background: There are several surgical treatment options available for comminuted intertrochanteric fractures but still, many controversies persist, as the postoperative complications increase with increased age. So, it is necessary to evaluate the role of hemiarthroplasty with cemented modular bipolar prosthesis in treating comminuted intertrochanteric fractures in elderly patients. The study aimed to analyse the functional outcomes of hemiarthroplasty with cemented modular bipolar prosthesis in comminuted fracture intertrochanteric femur in 42 elderly patients. Methods: In this observational prospective study, all patients were taken up for surgery within seven days of their injury. Assessment was done by the modified Harris Hip Score (HHS) during discharge and follow-up visits and results are analysed by paired t test. Results: There were 26 male and 16 female patients and a 50-50 % side distribution, with mean blood loss of 363.63 ml. Pre-injury ambulation, hypertension distribution analysis, diabetes distribution, hospital stay distribution analysis was done. Complications included superficial infection (14.29%), re-surgery (9.52%), limb length discrepancy seen in none of 76.19%, with a mean duration of surgery 95.86 minutes. The primary focus was the functional recovery as measured by the HHS. The average HHS improved progressively from 58.24 at discharge to 85.9 at 6 months, reflecting sustained recovery across all follow-up intervals. Conclusions: Cemented modular bipolar hemiarthroplasty is a highly effective treatment modality for elderly patients with unstable intertrochanteric fractures facilitating excellent functional recovery and minimizes complication rates.